Key Technologies for the Development of 100 J, 100 Hz Cryogenically-Cooled Active-Mirror Amplifier - Ogino, Jumpei; Fujioka, Kana; Kawanaka, Junji; Tokita, Shigeki; Zhaoyang, Li; Yamaguchi, Naohiro; Motokoshi, Shinji; Sakamoto, Masaaki; Morio, Noboru; Tsubakimoto, Koji; Yoshida, Hidetsugu (2019 Conference on Lasers and Electro-Optics Europe & European Quantum Electronics Conference (CLEO/Europe-EQEC), 2019)
Development of high-energy and high-repetition rate laser using Yb:YAG is a subject of growing attention to use many scientific and industrial applications. Especially, The Laser Wake Field Acceleration (LWFA) is receiving a lot of attention in the world [1-3]. Laser driven plasma accelerator (LPA) has potential to accelerate electron bunches to high energies in mm-size acceleration length, and still provides high quality bunch characteristics like: high bunch charge, femtosecond duration bunch length, and high pointing stability [4]. However, the accelerated electron charge is no many compare to radio frequency accretion. Therefore, the high repetition rate and high peak power laser is required. We have developed 1 J, 10 Hz cryogenically-cooled active mirror amplifier using Total-reflection active-mirror (TRAM) architecture [5]. At present, we are developing the 100 J, 100 Hz cryogenically-cooled active-mirror amplifier using Yb:YAG. The front end for the laser system is consists of CW distributed feedback laser diode, EO pulse slicer, which generates laser pulse of several ns duration at a pulse energy of few nJ. This pulse amplified up to around 200 mJ in the regenerative amplifier and multi-pass amplifiers using by cryogenically-cooled Yb:YAG. This pulse is amplified energy of 100J through two stage cryogenically-cooled active-mirror amplifier. We are developing the conductive cooled active mirror using the liquid nitrogen circulation. It is possible to 10kW (100J, 100Hz) operation. In order to conductive cooled active mirror, it is necessary to develop a cooling method for suppresses wave front changes in cooling. Therefore, we are developing Key technologies about cooling structure, bonding of amplifier medium and heat sink, wave front compensation. Also, we made the wave front measurement system of cryogenically-cooled active mirror. Figure. 1 (a) show the layout of wave front measurement system for cryogenically-cooled active mirror. The reference laser is fibre coupled CW distributed feedback laser diode at 1030 nm of wavelength. The reference laser is expanded to 50 m diameter by beam expander. The Yb:YAG coated AR and HR coat for 1030 nm. The Yb:YAG bonding at Heat-sink and cooling by cryocooler (Stirling cooler). The refracted laser is reduced to 5 mm diameter by beam reducer and input to the wave front sensor (SID4, PHASICS). Figure.1(b) show the measurement result of wave front shift. The wave front shift is change amount (P-V change) from the reference at room temperature (300K). The wave front shift increases with cooling, it is small value. Also, we measured the Zernike coefficient. It is dominant in low order and easy to compensation.